Electrochemical Characterization of Single Layer Graphene/Electrolyte Interface: Effect of Solvent on the Interfacial Capacitance. (11th March 2021) - Wu, Yih‐Chyng; Ye, Jianglin; Jiang, Gengping; Ni, Kun; Shu, Na; Taberna, Pierre‐Louis; Zhu, Yanwu; Simon, Patrice
Abstract: The development of the basic understanding of the charge storage mechanisms in electrodes for energy storage applications needs deep characterization of the electrode/electrolyte interface. In this work, we studied the charge of the double layer capacitance at single layer graphene (SLG) electrode used as a model material, in neat (EMIm‐TFSI) and solvated (with acetonitrile) ionic liquid electrodes. The combination of electrochemical impedance spectroscopy and gravimetric electrochemical quartz crystal microbalance (EQCM) measurements evidence that the presence of solvent drastically increases the charge carrier density at the SLG/ionic liquid interface. The capacitance is thus governed not only by the electronic properties of the graphene, but also by the specific organization of the electrolyte side at the SLG surface originating from the strong interactions existing between the EMIm + cations and SLG surface. EQCM measurements also show that the carbon structure, with the presence of sp 2 carbons, affects the charge storage mechanism by favoring counter‐ion adsorption on SLG electrode versus ion exchange mechanism in amorphous porous carbons. Abstract : The charge of the double layer capacitance at a single layer graphene (SLG) electrode was studied in neat (EMIm‐TFSI) and solvated (with acetonitrile) ionic liquid electrodes. Electrochemical impedance spectroscopy and gravimetric electrochemical quartz crystal microbalance measurements evidence that the presence of solvent drastically increases the charge carrier density at the SLG/ionic liquid interface.